2015
DOI: 10.3109/09593985.2015.1037874
|View full text |Cite
|
Sign up to set email alerts
|

Laserlight visual cueing device for freezing of gait in Parkinson’s disease: a case study of the biomechanics involved

Abstract: Keywords Background: Freezing of gait (FOG) is a serious gait disorder affecting up to two-thirds of people EMG, gait, kinematics, kinetics, Parkinson's with Parkinson's disease (PO). Cueing has been explored as a method of generating motor disease execution using visual transverse lines on the floor. However, the impact of a laser light visual cue remains unclear. Objective: To determine the biomechanical effect of a laser cane on FOG in History a participant with PO compared to a healthy age-and gender-match… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…In recent years, wearable laser lights have been designed to deal with FOG in PD patients. However, wearable laser lights failed to rescue FOG in some previous studies ( 28 30 ). Our results might explain this variability properly.…”
Section: Discussionmentioning
confidence: 82%
“…In recent years, wearable laser lights have been designed to deal with FOG in PD patients. However, wearable laser lights failed to rescue FOG in some previous studies ( 28 30 ). Our results might explain this variability properly.…”
Section: Discussionmentioning
confidence: 82%
“…In order to avoid studies with lower statistical power, 15 studies reporting samples with <10 patients were excluded. The therapies evaluated in those studies included visual cueing (laser light, staircase climbing) auditory cueing, tactile cueing, cueing exercise program, cognitive training, physical training, rTMS, and tDCS . All these approaches have been covered as well in the articles included in our review.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, although studies of laser cueing on gait in PD + FOG were further explored (5,17), few studies have revealed the effects of laser cueing on gait kinematicskinetics, especially in PD + FOG. Whether laser visual cueing may alleviate gait kinematics-kinetics remains unclear.…”
Section: Introductionmentioning
confidence: 99%